Shape-controllable nano metal oxide composite material and preparation method thereof
Through the coordination between polyphenols and metals, nanometal oxide composite materials with controllable shapes are prepared, which solves the problem of poor adsorption and selectivity caused by nanoparticle aggregation, and achieves efficient pollutant adsorption and good regeneration performance.
Patent Information
- Application Number
- CN202411904137.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
AI Technical Summary
The agglomeration of nanoparticles in existing nanometal oxide composite materials leads to problems such as blockage of pores and poor adsorption amount and selectivity.
By utilizing the coordination between polyphenols and metals, the particle size of nanometal oxides is limited to a small and uniform level, and its shape is adjusted to be spherical, reducing agglomeration and enhancing adsorption performance.
It has achieved good dispersion of nanometal oxide composite materials and excellent selective adsorption of target pollutants, improved treatment efficiency and processing capacity, and has good regeneration performance and practical application capabilities.
Smart Images

Figure CN119608124A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano composite materials, and in particular relates to a shape-controllable nano metal oxide composite material and a preparation method thereof. Background Art
[0002] Nano metal oxides have gradually become a research hotspot due to their large specific surface area and high selectivity for target pollutants. Among them, lanthanum oxide and zirconium oxide have received widespread attention in the fields of wastewater phosphorus removal, defluorination and resource recovery due to their relatively low price, environmental friendliness, stable chemical properties and rich surface hydroxyl groups. The shape of nano metal oxides has been shown to significantly affect the adsorption of phosphate / fluoride ions. For example, spherical nano lanthanum oxide has been shown to be more effective in removing pollutants than rod-shaped structures. Although shape-controllable nano metal oxides have great advantages in removing phosphate / fluoride ions, the surface energy increases significantly as the size of the metal oxide is reduced to the nanoscale, resulting in the agglomeration of nanoparticles, which leads to a decrease in the adsorption capacity of the nanoparticles. In addition, nanoparticles face problems such as poor mechanical strength, severe head loss, and difficulty in solid-liquid separation, and cannot be actually applied in fixed beds or flow systems.
[0003] In order to improve the feasibility of practical applications of nano-metal oxides, nano-metal oxides are often embedded in the pores of traditional porous structure carriers. This loading method not only takes advantage of the large specific surface area and easy operation of porous carriers, but also combines the high activity of nano-metal oxides, effectively improving the utilization rate of nanoparticles and realizing the engineering application of nanoparticles. Chinese patent application CN201410349969.X discloses a method for deep phosphorus removal using embedded lanthanum oxide composite resin. However, this type of technology also has shortcomings: (1) Nanoparticles loaded in porous carriers are very easy to agglomerate and cause pore blockage, thereby slowing the mass transfer rate of phosphate and reducing the utilization rate of nanoparticles; (2) Under this loading method, the shape of lanthanum oxide nanoparticles is uncontrollable, which affects the adsorption effect to a certain extent. Therefore, how to achieve good dispersion of nanoparticles in this type of composite material and excellent selective adsorption of target pollutants has become an urgent problem to be solved. Summary of the invention
[0004] Aiming at the problems of nanoparticles agglomerating to block pores and poor adsorption capacity and selectivity in existing nanometal oxide composite materials, the present invention discloses a shape-controllable nanometal oxide composite material and a preparation method thereof.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A shape-controllable nano metal oxide composite material comprises D201 resin and nano metal oxide loaded on the D201 resin, wherein the nano metal oxide is coordinated with polyphenol, the nano metal oxide is nano spherical particles with uniform size, and the polyphenol serves as a dispersant between the nano spherical particles.
[0007] As a preferred technical solution of the present invention, the diameter of the nano-spherical particles is less than 20 nm.
[0008] A method for preparing a shape-controllable nano-metal oxide composite material comprises the following steps:
[0009] S1, preparing a Tris buffer solution and anhydrous ethanol solution with a volume ratio of 10:3, wherein a certain amount of polyphenol is dissolved in the Tris buffer solution, and a certain amount of silane coupling agent is dissolved in the anhydrous ethanol solution, the above buffer solution and the anhydrous ethanol solution are mixed to form a mixed solution, and then the pretreated D201 resin is added to the mixed solution, and stirred at 25° C. for 12 hours, and after filtering, a resin material a modified by polyphenol and silane coupling agent can be obtained;
[0010] S2, dissolving a certain amount of metal salt in an ethanol aqueous solution, adding resin material a, stirring in a constant temperature water bath at 50°C for 12 hours, then stirring at 60°C for 6 hours and filtering to obtain product b;
[0011] S3, placing product b in a sodium hydroxide solution for in-situ precipitation, stirring for 12 h at 60° C., and filtering to obtain product c;
[0012] S4, the product c was washed with deionized water until it was neutral, and then the remaining RN in the product c was washed with a 5% sodium chloride solution. + (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral;
[0013] S5. Dry the product c treated to be neutral at 60° C. to obtain a nano-metal oxide composite material with a controllable shape.
[0014] As a preferred technical solution of the present invention, the polyphenol in step S1 is tannic acid (TA), and the mass volume ratio of tannic acid (TA) to Tris buffer solution is 10 g / L.
[0015] As a preferred technical solution of the present invention, the concentration of the Tris buffer solution in step S1 is 10 mM and the pH is 8.5.
[0016] As a preferred technical solution of the present invention, the silane coupling agent in step S1 is 3-aminopropyltriethoxysilane (APTES), and the mass volume ratio of 3-aminopropyltriethoxysilane (APTES) to anhydrous ethanol is 100g / 3L.
[0017] As a preferred technical solution of the present invention, the D201 resin pretreatment in step S1 is to sequentially wash it with 1 mol / L sodium hydroxide, 1 mol / L hydrochloric acid and 50% ethanol by volume to remove impurities therein, and finally dry it in an oven at 60°C for 24 hours for use.
[0018] As a preferred technical solution of the present invention, the metal salt in step S2 is a lanthanum (III) salt, or a zirconium (VI) salt, or a mixture of a lanthanum (III) salt and a lanthanum (III) salt.
[0019] As a preferred technical solution of the present invention, the ethanol aqueous solution in step S2 is an ethanol aqueous solution containing 20% by volume, and the mass volume ratio of the metal salt to the ethanol aqueous solution in step S2 is 100-150 g / L.
[0020] As a preferred technical solution of the present invention, the mass concentration of the sodium hydroxide solution in step S3 is 15%, and the mass concentration of the sodium chloride solution in step S4 is 5%.
[0021] The beneficial effects of the present invention are:
[0022] (1) The synthesis method of the present invention is simple, the raw materials (plant polyphenols) used are low-priced, the reagents are environmentally friendly and non-toxic, and it is convenient for mass production; the preparation method has strong universality and is suitable for the preparation of various nano-metal oxide composite materials.
[0023] (2) The present invention utilizes the coordination effect between polyphenols and metals to limit the particle size of nano metal oxides to a small and uniform level; at the same time, the shape of the nanoparticles is adjusted to a shape with optimal adsorption performance.
[0024] (3) Nano-metal oxides are loaded on macroporous polystyrene resin using the dispersibility of polyphenols, which reduces the agglomeration of nanoparticles. At the same time, polyphenols regulate the shape of nanoparticles to be spherical, which enhances the adsorption performance of nanoparticles.
[0025] (4) The nano-metal oxide composite material prepared by the present invention has excellent adsorption selectivity for phosphorus and fluorine in water, and has obvious advantages over unmodified composite materials, with high treatment efficiency and large treatment capacity.
[0026] (5) The nano-metal oxide composite material of the present invention has good regeneration performance and is easy to recycle. It maintains good practical application ability in a flowing water treatment system and has the ability of practical engineering application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a transmission electron microscope image of the nano-hydrated lanthanum oxide composite material La-201 prepared in Comparative Example 1 of the present invention and not modified with polyphenols;
[0028] Figure 2 This is a transmission electron microscope image of the nano-hydrated lanthanum oxide composite material La-TP-201 prepared in Example 1 of the present invention;
[0029] Figure 3 The performance of the shape-controllable nano-hydrated lanthanum oxide composite material La-TP-201 in removing phosphate from simulated wastewater;
[0030] Figure 4 The invention discloses the performance of the shape-controllable nano-hydrated lanthanum oxide composite material La-TP-201 in removing fluorine from water. DETAILED DESCRIPTION
[0031] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0032] Functional materials constructed by surface modification and functionalization of polyphenols have good dispersibility and biocompatibility, which can fully improve the adsorption performance of functional materials. Tannic acid (TA) is widely available and easy to obtain, and contains rich catechol and pyrogallol groups. These structures can be further self-assembled with various molecules and groups through hydrogen bonds and other methods and deposited on the surface of the material. Tannic acid can coordinate with metals and can be used as a cornerstone for adjusting the morphology of nanoparticles, and this process is related to the hydroxyl group in the molecular structure of tannic acid. Therefore, functional materials modified with polyphenols are expected to solve the drawbacks of nano-metal oxide composite materials. At present, the existing patent CN110026161A discloses a polymer-based nano-hydrated lanthanum oxide material, a method for controlling the crystal form and crystallinity, an application and a regeneration method, but there are few reports on the research of regulating the shape of nanoparticles in the composite material. Therefore, based on the above content, the present invention mainly utilizes the coordination between polyphenols and metals to disperse metal oxides on the anion exchange resin D201 mediated by TA-APTES to prepare a shape-controllable nano-metal oxide composite material, and is used for the deep removal of phosphate and fluoride ions in water. The nano metal oxide is nano spherical particles with uniform size, and the polyphenol is used as a dispersant between the nano spherical particles, and the diameter of the nano spherical particles is less than 20nm.
[0033] The following chemicals are mainly used in this application:
[0034] D201 resin (Specifications: quaternary ammonium type D201 strong base anion exchange resin; manufacturer: Ningbo Zhengguang Resin Co., Ltd.)
[0035] Lanthanum chloride hexahydrate (purity: AR, 99.99%; manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.)
[0036] Zirconium oxychloride octahydrate (Purity: AR, 98%; Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.)
[0037] Tannic acid (TA) (purity: AR; manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.)
[0038] 3-Aminopropyltriethoxysilane (APTES) (Purity: AR, 98%; Manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd.)
[0039] The D201 resin in all comparative examples and examples was pretreated by washing with 1 mol / L sodium hydroxide, 1 mol / L hydrochloric acid and 50% ethanol by volume to remove impurities, and finally dried in an oven at 60°C for 24 hours before use. Determination of material loading rate:
[0040] The obtained material was acidified and digested in a nitric acid-perchloric acid system, the La / Zr element content in the solution was determined by inductively coupled plasma (ICP) emission spectrometry, and the loading amount of nano-hydrated lanthanum oxide / zirconium in the composite material (based on the mass of La / Zr) was calculated according to formula (1).
[0041]
[0042] Wherein C (mg / L) and V (L) represent the concentration and volume of La / Zr in the digestion solution, M (g / mol) is the molar mass, wherein M1 is the molar mass of nano-lanthanum oxide / zirconium oxide, M2 is the molar mass of La / Zr element, m (mg) is the mass of the composite material, and the composite materials in the comparative examples and embodiments are digested and the metal loading rate in the composite material is calculated according to this method.
[0043] Comparative Example 1
[0044] The specific preparation process of the nano-hydrated lanthanum oxide composite material without polyphenol modification is as follows:
[0045] S1. Dissolve 20 g of lanthanum chloride hexahydrate in 200 mL of 20% ethanol aqueous solution, add 20 g of pretreated D201 resin, stir continuously in a constant temperature water bath at 50° C. for 12 h, then stir at 60° C. for 6 h, and filter to obtain product d;
[0046] S2. In order to convert the metal lanthanum oxide on the product d into nano-hydrated lanthanum oxide, the product d was placed in a sodium hydroxide solution with a mass concentration of 15% for in-situ precipitation, and the product e was obtained after being fully stirred at 60° C. for 12 hours;
[0047] S3, the product e was washed with deionized water until it was neutral, and then the remaining RN in the product e was removed with a 5% sodium chloride solution. + (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral;
[0048] S4, drying the neutralized product e at 60°C to obtain the target nano-hydrated lanthanum oxide composite material La-201. The nano-hydrated lanthanum oxide loading is 4.1%, and the loading in the subsequent examples and comparative example 1 is maintained at 4-5%. Figure 1 As shown, the lanthanum oxide in the nano-hydrated lanthanum oxide composite material La-201 prepared in Comparative Example 1 presents a rod-like morphology.
[0049] Example 1
[0050] The specific preparation process of a shape-controllable nano-hydrated lanthanum oxide composite material is as follows:
[0051] S1. Weigh 10 g of TA and dissolve it in 1000 mL of Tris (10 mM, pH = 8.5) buffer solution (the mass volume ratio of tannic acid (TA) to Tris buffer solution is 10 g / L), weigh 10 g of APTES and dissolve it in 300 mL of anhydrous ethanol (the mass volume ratio of 3-aminopropyltriethoxysilane (APTES) to anhydrous ethanol is 100 g / 3L), and mix the above two solutions to prepare a mixed solution, then add 20 g of pretreated D201 resin to the mixed solution and stir at 25° C. for 12 h, and filter to obtain TA-APTES modified resin material a;
[0052] S2, dissolving 20 g of lanthanum chloride hexahydrate in 200 mL of 20% ethanol aqueous solution, adding resin material a, stirring continuously in a constant temperature water bath at 50° C. for 12 h, then stirring at 60° C. for 6 h, filtering to obtain product b;
[0053] S3. In order to convert the metal lanthanum oxide on the product b into nano-hydrated lanthanum oxide, the product b is placed in a sodium hydroxide solution with a mass concentration of 15% for in-situ precipitation, and the product c is obtained after being fully stirred at 60° C. for 12 hours;
[0054] S4, the product c was washed with deionized water until it was neutral, and then the remaining RN in the product c was washed with a 5% sodium chloride solution. + (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral;
[0055] S5, drying the neutralized product c at 60°C to obtain a nano-hydrated lanthanum oxide composite material La-TP-201 (wherein La represents lanthanum oxide and TP represents TA-APTES) with a controllable shape, wherein the nano-hydrated lanthanum oxide loading is 4.3%. Figure 2 As shown, the lanthanum oxide in the nano-hydrated lanthanum oxide composite material La-TP-201 prepared in Example 1 presents a spherical morphology.
[0056] Example 2
[0057] The specific preparation process of a shape-controllable nano-hydrated zirconium oxide composite material is as follows:
[0058] S1. Weigh 10 g of TA and dissolve it in 1000 mL of Tris (10 mM, pH = 8.5) buffer solution (the mass volume ratio of tannic acid (TA) to Tris buffer solution is 10 g / L), weigh 10 g of APTES and dissolve it in 300 mL of anhydrous ethanol (the mass volume ratio of 3-aminopropyltriethoxysilane (APTES) to anhydrous ethanol is 100 g / 3L), and mix the above two solutions to prepare a mixed solution, then add 20 g of pretreated D201 resin to the mixed solution and stir at 25° C. for 12 h, and filter to obtain TA-APTES modified resin material a;
[0059] S2, dissolving 30g of zirconium oxychloride octahydrate in 200mL of an aqueous solution containing 20% by volume ethanol and 5% by mass hydrochloric acid (due to the low dielectric constant of ethanol, most of the Zr(IV) precursor is in the form of a neutral ion pair. Compared with Example 1, hydrochloric acid is required in this case to adjust the zirconium oxide to form [Zr4(OH)8(OH2) 16 ] 8+ tetramer), add resin material a, stir continuously in a constant temperature water bath at 50°C for 12 h, then stir at 60°C for 6 h, and filter to obtain product b;
[0060] S3. In order to convert the metal zirconium oxide on the product b into nano-hydrated zirconium oxide, the product b was placed in a sodium hydroxide solution with a mass concentration of 15% for in-situ precipitation, and the product c was obtained after being fully stirred at 60° C. for 12 hours.
[0061] S4, the product c was washed with deionized water until it was neutral, and then the remaining RN in the product c was washed with a 5% sodium chloride solution. + (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral;
[0062] S5. Dry the neutralized product c at 60°C to obtain a nano-hydrated zirconium oxide composite material Zr-TP-201 (wherein Zr represents zirconium oxide and TP represents TA-APTES) with a controllable shape, wherein the nano-hydrated zirconium oxide loading is 4.8%.
[0063] Example 3
[0064] The specific preparation process of a shape-controllable nano-lanthanum-zirconium bimetallic composite material is as follows:
[0065] S1. Weigh 10 g of TA and dissolve it in 1000 mL of Tris (10 mM, pH = 8.5) buffer solution (the mass volume ratio of tannic acid (TA) to Tris buffer solution is 10 g / L), weigh 10 g of APTES and dissolve it in 300 mL of anhydrous ethanol (the mass volume ratio of 3-aminopropyltriethoxysilane (APTES) to anhydrous ethanol is 100 g / 3L), and mix the above two solutions to prepare a mixed solution, then add 20 g of pretreated D201 resin to the mixed solution and stir at 25° C. for 12 h, and filter to obtain TA-APTES modified resin material a;
[0066] S2, 10g of lanthanum chloride hexahydrate and 15g of zirconium oxychloride octahydrate were dissolved in 200mL of an aqueous solution containing 20% by volume ethanol and 5% by mass hydrochloric acid (due to the low dielectric constant of ethanol, most of the Zr(IV) precursors are neutral ion pairs. Compared with Example 1, hydrochloric acid is required to adjust the zirconium oxide to form [Zr4(OH)8(OH2) 16 ] 8+ tetramer), add resin material a, stir continuously in a constant temperature water bath at 50°C for 12 h, then stir at 60°C for 6 h, and filter to obtain product b;
[0067] S3. In order to convert the metal lanthanum and zirconium oxides on the product b into nano-hydrated lanthanum oxide and nano-hydrated zirconium oxide, the product b is placed in a sodium hydroxide solution with a mass concentration of 15% for in-situ precipitation, and the product c is obtained after being fully stirred at 60° C. for 12 hours;
[0068] S4, the product c was washed with deionized water until it was neutral, and then the remaining RN in the product c was washed with a 5% sodium chloride solution.+ (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral;
[0069] S5. The neutralized product c is placed at 60°C and dried to obtain a nano-hydrated lanthanum zirconium oxide bimetallic composite material LaZr-TP-201 (wherein La represents lanthanum oxide, Zr represents zirconium oxide, and TP represents TA-APTES) with a controllable shape. The loading amounts of nano-hydrated lanthanum oxide and hydrated zirconium oxide are 2.1% and 2.1%, respectively.
[0070] Example 4
[0071] Phosphate adsorption experiment of shape-controlled nano-hydrated lanthanum oxide composites in the presence of competing ions:
[0072] 114.5 mg of sodium sulfate (the concentration of sodium sulfate in the mixed solution is 1548.4 mg / L) was added as a competitive ion to 50 mL of a phosphate solution with a concentration of 25 mg / L, wherein the molar ratio of sulfate to phosphate was 20, and 25 mg of the La-TP-201 composite material in Example 1 and 25 mg of the La-201 composite material in Comparative Example 1 were added to two conical flasks respectively, and the mixture was moved to a 25°C constant temperature water bath oscillator and oscillated at a speed of 140 r / min for equilibrium, and then taken out, the phosphate concentration in the solution after equilibrium was measured, and the influence of the competitive ions on the adsorption of phosphate by the composite material was analyzed. As shown in Table 1, under the condition of high concentration of competitive ions, the polyphenol-modified nano-hydrated lanthanum oxide composite material La-TP-201 has stronger adsorption selectivity, and its K d K for La-201 d 7.1 times of that.
[0073] Table 1 Selective distribution coefficients of phosphorus removal of La-TP-201 and La-201 composite materials with and without competing ions
[0074]
[0075] Example 5
[0076] Effect of shape-controlled nano-hydrated lanthanum oxide composites on phosphorus removal from simulated wastewater:
[0077] Prepare 5L of simulated wastewater with a phosphate concentration of 2mg / L and a chloride ion, sulfate ion, and nitrate ion (sodium chloride, sodium sulfate, and sodium nitrate are used to provide chloride ions, sulfate ions, and nitrate ions as competitive ions) concentration of 100mg / L. The pH of the solution is adjusted to 6.2±0.3. Measure 5mL of the wet volume (the volume occupied by the material in the water component) of the La-TP-201 composite material in Example 1 and load it into a glass adsorption column (i.e., bed volume 1BV=5mL), use a peristaltic pump to pass the simulated wastewater through the material from top to bottom at a constant speed, and use an automatic sample collector to collect water samples, such as Figure 3 As shown, when the effluent concentration reaches the breakthrough point of 0.5 g / L, the treated water volume can reach 3790 BV, which can operate stably in the flow system and has good practical application potential.
[0078] Example 6
[0079] Static adsorption-desorption cycle experiment of fluorine removal by shape-controlled nano-hydrated lanthanum oxide composite material:
[0080] Add 50 mL of fluorine solution with an initial concentration of 25 mg / L into a conical flask, weigh 25 mg of the La-TP-201 composite material in Example 1 into the conical flask, place it in a constant temperature water bath oscillator to fully oscillate and balance, then take out some water samples for testing; desorb the reacted material with a binary solution of 7.5% NaOH-5% NaCl by mass concentration, measure the phosphate concentration after equilibrium, and calculate its regeneration rate. Wash the remaining composite material with deionized water until it is neutral. The above steps are regarded as one cycle and repeated five times to evaluate the reusability of the composite material. Figure 4 As shown, after five cycles, the decrease in the adsorption of fluoride ions was negligible, maintaining excellent cyclic performance.
[0081] Example 7
[0082] Static adsorption experiment of shape-controlled nano-hydrated zirconium oxide composites for removing phosphate:
[0083] Phosphate solutions of 10, 20, and 50 mg / L were prepared, and 50 mL of the above solutions were taken and placed in 150 mL conical flasks, and 25 mg of the Zr-TP-201 composite material in Example 2 was added to the flasks, and the phosphate concentration in the adsorbed solution was measured after oscillation equilibrium in a constant temperature water bath oscillator. As shown in Table 2, the removal rate of the composite material for 10 and 20 mg / L phosphate was close to 100%, maintaining good removal performance.
[0084] Table 2 Phosphate removal performance of shape-controlled nano-hydrated zirconium oxide composites
[0085]
[0086] Example 8
[0087] Static adsorption experiment of shape-controlled nano-lanthanum-zirconium bimetallic composites to remove phosphate:
[0088] A phosphate solution with a volume of 50 mL and an initial concentration of 10, 20, and 50 mg / L was prepared, and the above solution was placed in a 150 mL conical flask, and 25 mg of the LaZr-TP-201 bimetallic composite material in Example 3 was added to the flask, and the phosphate concentration in the adsorbed solution was measured after oscillation equilibrium in a constant temperature water bath oscillator. As shown in Table 3, the removal rate of the composite material for 10 and 20 mg / L phosphate was close to 100%, maintaining good removal performance, and was better than the single metal composite material.
[0089] Table 3 Phosphate removal performance of shape-controlled nano-lanthanum-zirconium bimetallic composites
[0090]
[0091] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A shape-controllable nano-metal oxide composite material, characterized in that: The invention comprises D201 resin and nano metal oxide loaded on the D201 resin, wherein the nano metal oxide is coordinated with polyphenol, the nano metal oxide is nano spherical particles with uniform size, and the polyphenol is used as a dispersant between the nano spherical particles.
2. The shape-controllable nano-metal oxide composite material according to claim 1, characterized in that: The diameter of the nano spherical particles is less than 20 nm.
3. A method for preparing a shape-controllable nano-metal oxide composite material according to any one of claims 1 to 2, characterized in that: The steps include: S1, preparing a Tris buffer solution and anhydrous ethanol solution with a volume ratio of 10:3, wherein a certain amount of polyphenol is dissolved in the Tris buffer solution, and a certain amount of silane coupling agent is dissolved in the anhydrous ethanol solution, the above buffer solution and the anhydrous ethanol solution are mixed to form a mixed solution, and then the pretreated D201 resin is added to the mixed solution, and stirred at 25° C. for 12 hours, and after filtering, a resin material a modified by polyphenol and silane coupling agent can be obtained; S2, dissolving a certain amount of metal salt in an ethanol aqueous solution, adding resin material a, stirring in a constant temperature water bath at 50°C for 12 hours, then stirring at 60°C for 6 hours and filtering to obtain product b; S3, placing product b in a sodium hydroxide solution for in-situ precipitation, stirring for 12 h at 60° C., and filtering to obtain product c; S4, the product c was washed with deionized water until it was neutral, and then the remaining RN in the product c was washed with a 5% sodium chloride solution. + (CH3)3·OH - Convert to RN + (CH3)3·Cl - , and finally washed with 50% ethanol by volume until neutral; S5. Dry the product c treated to be neutral at 60° C. to obtain a nano-metal oxide composite material with a controllable shape.
4. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: In step S1, the polyphenol is tannic acid (TA), and the mass volume ratio of tannic acid (TA) to Tris buffer solution is 10 g / L.
5. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: The concentration of the Tris buffer solution in step S1 is 10 mM, and the pH is 8.
5.
6. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: In the step S1, the silane coupling agent is 3-aminopropyltriethoxysilane (APTES), and the mass volume ratio of 3-aminopropyltriethoxysilane (APTES) to anhydrous ethanol is 100 g / 3 L.
7. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: The D201 resin pretreatment in step S1 is to be washed with 1 mol / L sodium hydroxide, 1 mol / L hydrochloric acid and 50% ethanol in order to remove impurities, and finally dried in an oven at 60° C. for 24 hours before use.
8. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: The metal salt in step S2 is a lanthanum (III) salt, or a zirconium (VI) salt, or a mixture of a lanthanum (III) salt and a lanthanum (III) salt.
9. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: The aqueous solution of ethanol in step S2 is an aqueous solution containing ethanol with a volume fraction of 20%, and the mass volume ratio of the metal salt to the aqueous solution of ethanol in step S2 is 100-150 g / L.
10. The method for preparing a shape-controllable nano-metal oxide composite material according to claim 3, characterized in that: The mass concentration of the sodium hydroxide solution in step S3 is 15%, and the mass concentration of the sodium chloride solution in step S4 is 5%.
Citation Information
Patent Citations
A method for deep phosphorus removal using embedded lanthanum oxide composite resin
CN104138750B
Polymer-based nano lanthanum oxide hydrate material, crystal form and crystallinity regulation and control method, application and regeneration method
CN110026161A
Textile of rapid self-purification chemical warfare agent simulant and preparation method of textile
CN112048920A
Plant polyphenol mediated carbon-based metal oxide and preparation method thereof
CN118217944A